Determination of urinary aldosterone using a plasma aldosterone 2D ID LC–MS/MS method. (September 2016) - Bekkach, Yasin; Heijboer, Annemieke C; Endert, Erik; Ackermans, Mariëtte T
Aim: In the diagnosis for primary aldosteronism, the measurement of urinary aldosterone is part of the confirmation test but diagnostic accuracy may be blunted due to poor immunoassay performance for urinary aldosterone. Nowadays, plasma aldosterone concentrations are measured preferably by LC–MS/MS yet such methods for urinary aldosterone are lacking.Methods & results: We show that plasma and urinary aldosterone can be measured with the same 2D isotope dilution LC–MS/MS method. The accuracy of the method was tested against a certified reference material. The reference values for plasma and urinary aldosterone were established.Discussion & conclusion: With this method, urinary aldosterone concentrations can be measured precisely, simply and accurately together with plasma samples with one set of calibration standards.